Red and White Never Looked So Good: Social Media Monitoring of Erspo via Brand24 - Shaffira, Nadya; Setianti, Yanti; Warta, Waska (Jurnal Komunikasi Global, 2025)
Erspo, the newly appointed official apparel supplier for the Indonesian National Football Team, has gained widespread attention. The role of social media influencers, particularly on platforms like TikTok and X has significantly amplified the brands visibility. By using Agenda Setting Theory, this study aims to analyze Erspos brand image amid public opinion through media monitoring and sentiment analysis using Brand24. This quantitative study collected data from social media and online media during the period 15 October to 15 November 2024, focusing on how frequently and widely the brand is discussed, and how public sentiment is distributed. The results show that 55% of the sentiment was positive, dominated by appreciation for the jersey design and Erspos role as the official apparel of the Indonesian National Team. Meanwhile, 45% of the sentiment was negative, triggered by complaints about product quality and a controversial statement from the national team coach. TikTok recorded the highest reach (2.78 million users), while X generated the most mentions (375 mentions). Public discussion was driven by three major issues, including product quality, team performance, and sports governance. This study concludes that brand reputation is highly influenced by issue salience and content frequency across platforms.Erspo, yang baru saja ditunjuk sebagai pemasok resmi apparel Tim Nasional Sepak Bola Indonesia, telah menarik perhatian luas. Peran influencer media sosial, terutama di platform seperti TikTok dan X, secara signifikan meningkatkan visibilitas merek ini. Dengan menggunakan Teori Agenda Setting, penelitian ini bertujuan untuk menganalisis citra merek Erspo di tengah opini publik melalui pemantauan media dan analisis sentimen menggunakan Brand24. Penelitian kuantitatif ini mengumpulkan data dari media sosial dan media daring selama periode 16 Oktober hingga 15 November 2024, dengan fokus pada seberapa sering dan luas merek tersebut dibahas, dan bagaimana sentimen publik didistribusikan. Hasil penelitian menunjukkan bahwa 55% sentimen bersifat positif, didominasi oleh apresiasi terhadap desain jersey dan peran Erspo sebagai apparel resmi Timnas Indonesia. Sementara itu, 45% sentimen bersifat negatif, dipicu oleh keluhan tentang kualitas produk dan pernyataan kontroversial dari pelatih timnas. TikTok mencatat jangkauan tertinggi (2,78 juta pengguna), sementara X menghasilkan mention terbanyak (375 mention). Diskusi publik didorong oleh tiga isu utama, yaitu kualitas produk, kinerja tim, dan tata kelola olahraga. Penelitian ini menyimpulkan bahwa reputasi merek sangat dipengaruhi oleh saliensi isu dan frekuensi konten di seluruh platform.